Slow Moving Dreams - Hardy, Tom (Tom J.) (Book collections on Project MUSE., 2011)
Tom Hardy's new novel, Slow Moving Dreams, tells the story of Tom Carter, a city man who is forced by the death of a cousin to return to his rural roots in West Texas. Hardy takes his readers along two journeys in this novel: the first is the physical journey that Tom takes as he drives to the funeral in Alpine, and the second is an exploration of Tom's life as a child growing up in the country that the adult Tom is now passing through. But not all of those memories are happy ones, as Tom and his cousins soon find out. The funeral starts to unravel a dark secret that could change everythin.